EFEKTIVITAS MGMP DI MADRASAH ALIYAH NEGERIMAMUJU PROVINSI SULAWESI BARAT - Amiruddin Amiruddin (Al-Qalam, 2009)
The research aims to describe the effectiveness of MGMP in MAN Mamuju,west Sulawesi province. Result shows that generally the implementationof MGMP in MAN Mamuju is quite effective. However, the teachersthought that it lacked government support and result in its low quality.MGMP is an institution where the teacher can discuss the learningsystem on the courses in school. To improve the quality of the discussionwhich can increase the capability of the teacher on learning and syllabusdevelopment method, the support of government and other institutionis required.